The current status of Neocnus Arredondo, 1961 (Mammalia: Edentata: Pilosa: Megalonichidae) and a replacement name for its junior homonym in the sea cucumber family Cucumariidae (Echinodermata :Holothuroidea: Dendrochirotida: Cucumariidae) - Thandar, Ahmed S.; Vinola, Lazaro W. V. (Zootaxa, 2017)
This short communication addresses the problem associated with the current taxonomic status of the prehistoric edentate genus Neocnus Arredondo, 1961 (with type species Micronocnus gliriformis Matthew, 1931) which has long been considered a senior homonym of the dendrochirotid sea cucumber genus Neocnus Cherbonnier, 1972 (type species Neocnus incubans Cherbonnier, 1972) and replaces the latter (junior homonym) with Incubocnus n.g. The diagnosis of the new genus is the same as the cucumariid Neocnus as amended by O’Loughlin & O’Hara (1992). A brief history of the senior homonym Neocnus (Edentata) is given followed by a short literature survey dealing with its junior homonym.